Extent of Systems Performance of Caraga State University, Butuan City, Mindanao, Philippines - Alvaro L. Salingay (Philippine Association of Institutions for Research, Inc., 2012)
This study adopted a descriptive survey design to assess the extent of systems performance processes of Caraga State University in Butuan City, Mindanao, Philippines with the aim of gauging the extent of systems performance processes as rated by 164 respondents consisting of 38 Administrators, 71 Faculty Members and 55 Non-academic Staff. Results show that the school's extent of systems performance processes was moderately achieved. The different perception of respondents on the extent of systems performance processes shows incongruence of perceptions among administrators, faculty and staff that leads to the gap in understanding the degree of university performance with regards to the financial aspects, customer satisfaction, internal business process efficiency and learning and innovation. The school needs to improve its processes especially its processes on customer satisfaction, internal business process efficiency and learning and innovation to improve its financial performance.